2016
DOI: 10.1093/ntr/ntw140
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Cigarette Smoking With Depression and Anxiety: A Systematic Review

Abstract: Background:Many studies report a positive association between smoking and mental illness. However, the literature remains mixed regarding the direction of this association. We therefore conducted a systematic review evaluating the association of smoking and depression and/or anxiety in longitudinal studies.Methods:Studies were identified by searching PubMed, Scopus, and Web of Science and were included if they: (1) used human participants, (2) were longitudinal, (3) reported primary data, (4) had smoking as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
515
6
37

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 880 publications
(688 citation statements)
references
References 170 publications
57
515
6
37
Order By: Relevance
“…This is consistent with the findings of a study done by El‐Mallakh et al, which showed a significant correlation between cigarette smoking and psychological disorders such as anxiety. On a systematic review of 148 studies regarding the association of cigarette smoking with depression and anxiety, the results varied considerably but few studies supported a bidirectional relationship with evidence for smoking to be both associated with subsequent depression and anxiety, and vice versa . The effect sizes and odds ratios of this finding suggest that it has a low to moderate clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of a study done by El‐Mallakh et al, which showed a significant correlation between cigarette smoking and psychological disorders such as anxiety. On a systematic review of 148 studies regarding the association of cigarette smoking with depression and anxiety, the results varied considerably but few studies supported a bidirectional relationship with evidence for smoking to be both associated with subsequent depression and anxiety, and vice versa . The effect sizes and odds ratios of this finding suggest that it has a low to moderate clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Although current data do not permit explication of a causal effect between smoking and depression, numerous studies suggest that smoking is associated with increased risk of the onset (Fergusson et al, 2003) and persistence (Bakhshaie et al, 2015) of depression, though the direction of effect cannot be examined here and while some data suggest depression is associated with smoking relapse (Zvolensky et al, 2015) other studies suggest no link between depression and relapse to smoking (Taylor et al, 2015). A nearly equal number of studies (Fluharty et al 2016) suggest the reverse pathway (Taylor et al, 2014); the relation appears to be bi-directional and possible mechanisms are not well understood (Goodwin (In Press). To ensure timely and effective prevention and treatment efforts, additional work should focus on elucidating targetable underlying factors associated with both forms of the smoking-depression relation.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine, the major addictive component of tobacco, binds to and activates/desensitize nicotinic acetylcholine receptors (nAChRs) to elicit neural responses (see Box 2). Acutely, nicotine can induce a relief of anxiety and sustain tobacco use through positive emotional reinforcement (see also [8, 9]). The activation of circuits mediating the anxiolytic effects of nicotine may be considered an attempt at self-medication in people with ADs [10].…”
Section: Anxiety Disorders and Their Comorbidity With Nicotine Dependmentioning
confidence: 99%